2011
DOI: 10.1073/pnas.1102444108
|View full text |Cite
|
Sign up to set email alerts
|

Mutant alcohol dehydrogenase leads to improved ethanol tolerance in Clostridium thermocellum

Abstract: Clostridium thermocellum is a thermophilic, obligately anaerobic, Gram-positive bacterium that is a candidate microorganism for converting cellulosic biomass into ethanol through consolidated bioprocessing. Ethanol intolerance is an important metric in terms of process economics, and tolerance has often been described as a complex and likely multigenic trait for which complex gene interactions come into play. Here, we resequence the genome of an ethanol-tolerant mutant, show that the tolerant pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
146
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(160 citation statements)
references
References 58 publications
14
146
0
Order By: Relevance
“…The phylogenetically related, thermophilic Firmicute C. thermocellum, however, encodes an NADH-dependent AdhE (Cthe0423), which is one of the most highly expressed genes (24) and abundant proteins (25) in C. thermocellum and is the key enzyme in ethanol production in this organism. Based on its known thermostability, coenzyme specificity (NADH-dependent), similarity in codon use, and favorable catalytic stoichiometry (26), this adhE was a promising candidate to generate an ethanol production pathway in C. bescii. The adhE gene from C. thermocellum was expressed in the C. bescii ldh mutant strain (JWCB018), resulting in strain C. bescii JWCB032 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetically related, thermophilic Firmicute C. thermocellum, however, encodes an NADH-dependent AdhE (Cthe0423), which is one of the most highly expressed genes (24) and abundant proteins (25) in C. thermocellum and is the key enzyme in ethanol production in this organism. Based on its known thermostability, coenzyme specificity (NADH-dependent), similarity in codon use, and favorable catalytic stoichiometry (26), this adhE was a promising candidate to generate an ethanol production pathway in C. bescii. The adhE gene from C. thermocellum was expressed in the C. bescii ldh mutant strain (JWCB018), resulting in strain C. bescii JWCB032 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…‡ Cthe-adhE (Cthe0423; Bifunctional acetaldehyde/alcohol dehydrogenase derived from Clostridium thermocellum ATCC27405). § Cthe-adhE*(EA) (Cthe0423-P704L,H734R: Bifunctional acetaldehyde-CoA/alcohol dehydrogenase derived from ethanol tolerant Clostridium thermocellum strain EA) (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have confirmed the feasibility to manipulate some cellulytic microorganisms e.g. Clostridium (Brown et al, 2011) and Thermobifida spp. (Deng and Fong, 2011).…”
Section: Strategies To Design Ideal Microorganisms For Cbpmentioning
confidence: 95%
“…A high concentration of ethanol itself is an inhibiting factor to microorganisms, and therefore ethanol tolerant strains are being investigated. Brown et al (2011) resequenced the genome of an ethanol-tolerant Clostridium thermocellum mutant, and showed that the tolerant phenotype is primarily due to a mutated bifunctional acetaldehyde-CoA/alcohol dehydrogenase gene (adhE). Biochemical assays confirmed a complete loss of NADHdependent activity with concomitant acquisition of NADPHdependent activity, which, they conclude, likely affects electron flow in the mutant.…”
mentioning
confidence: 99%